Morphological properties of flocs under turbulent break‐up and restructuring processes. Issue 9 (14th April 2017) - Vlieghe, M.; Frances, C.; Coufort‐Saudejaud, C.; Liné, A.
Abstract : Bentonite flocculation was performed in a Taylor–Couette reactor coupled with an in situ method of image acquisition and analysis. A hydrodynamic sequencing is imposed to perform successive cycles of flocculation and breakage. Depending on the shear rate applied during the breakage step, one or two cycles are needed after the first flocculation step to recover a full reversibility on both size and shape factors. The breakup step produces flocculi that are the building blocks for the next. The re‐flocculation steps produce smaller sizes and more regular shapes than the initial growth step. The floc size is calibrated by the turbulence as the radius of gyration is close to the Kolmogorov microscale whereas the floc structure is determined by flocculi aggregates. An analysis of the change of the flocs morphology, despite of their diversity, can also be achieved thanks to some relevant moments of the distributions. © 2017 American Institute of Chemical Engineers AIChE J, 63: 3706–3716, 2017